Democratizing Local Legislation Through Public Participation: A Critical Analysis of Regulations in Central Sulawesi - Mohamad Safrin; Andi Reza Alief; Irzha Friskanov S (Fakultas Syariah INSURI Ponorogo, 2026)
This study critically examines the legal dimensions, mechanisms, and barriers to public participation in the formulation of local regulations (perda) in Central Sulawesi. Employing a socio-legal approach that integrates normative analysis with empirical inquiry, the research evaluates compliance with the 1945 Constitution, Law No. 12/2011 (amended by Law No. 15/2019), Law No. 23/2014, and Ministry of Home Affairs Regulation No. 80/2015. Empirical data were gathered through in-depth interviews with 45 informants, observations at 12 public consultation forums, and document analysis of three strategic local regulations across four regions during 2021–2023. The findings reveal a significant implementation gap: public participation has been reduced to procedural formality, fundamentally contradicting the principle of openness. Three critical legal deficits were identified: (1) the absence of legal sanctions for procedural participation violations; (2) insufficient clarity in mechanisms for substantively accommodating public input; and (3) the lack of a public right of action against regulations enacted without adequate participation. The study concludes that multidimensional legal reform, coupled with a community-based deliberative participation model, is essential to fostering authentic and equitable democratization within the local legislative process.